Antiviral activity of the dichloromethane extracts from Artocarpus heterophyllus leaves against hepatitis C virus - Achmad Fuad Hafid; Chie Aoki-Utsubo; Adita Ayu Permanasari; Myrna Adianti; Lydia Tumewu; Aty Widyawaruyanti; Sri Puji Astuti Wahyuningsih; Tutik Sri Wahyuni; Maria Inge Lusida; Soetjipto; Hak Hotta (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To determine anti-viral activities of three Artocarpus species: Artocarpus altilis, Artocarpus camansi, and Artocarpus heterophyllus (A. heterophyllus) against Hepatitis C Virus (HCV). Methods: Antiviral activities of the crude extracts were examined by cell culture method using Huh7it-1 cells and HCV genotype 2a strain JFH1. The mode of action for anti-HCV activities was determined by time-of-addition experiments. The effect on HCV RNA replication and HCV accumulation in cells were analyzed by quantitative reverse transcription-PCR and western blotting, respectively. Results: The dichloromethane (DCM) extract of A. heterophyllus exhibited strong anti-HCV activity with an inhibitory concentration (IC50) value of (1.5 ± 0.6) μg/mL without obvious toxicity. The DCM extracts from Artocarpus altilis and Artocarpus camansi showed moderate anti-HCV activities with IC50 values being (6.5 ± 0.3) μg/mL and (9.7 ± 1.1) μg/mL, respectively. A time-of-addition studies showed that DCM extract from A. heterophyllus inhibited viral entry process though a direct virucidal activity and targeting host cells. HCV RNA replication and HCV protein expression were slightly reduced by the DCM treatment at high concentration. Conclusions: The DCM extract from A. heterophyllus is a good candidate to develop an antiviral agent to prevent HCV grant reinfection following liver transplantation.